NURSES’ PERCEPTIONS REGARDING DIGITAL-BASED NURSING CARE DOCUMENTATION IN THE OUTPATIENT INSTALLATION OF THE SUMEDANG REGIONAL GENERAL HOSPITAL, WEST JAVA - Salpani,; Ningrum, Dedah; Haryeti, Popon (Buletin Veteriner Udayana, 2024)
With the Minister of Health Regulation Number 24 of 2022 concerning medical records which emphasizes more authority for the government to regulate electronic medical records. Sumedang Regional Hospital implements these regulations, therefore researchers are interested in examining nurses' perceptions about digital-based nursing care documentation. The aim of this research is to find out nurses' perceptions regarding digital-based nursing care documentation. The research method used is a qualitative approach with interview data collection techniques recorded on a cellphone. The result of this research is that digital-based documentation of nursing care becomes a burden for nurses. The nurse stated that digital-based documentation of nursing care has advantages and disadvantages that are felt by nurses. The advantages felt by nurses are that they are faster and more effective, while the disadvantages felt by nurses are network disruption and system errors which will hinder work, even during the transition period nurses find it difficult and adaptation takes time. The conclusion of this research is that nurses are burdened with documenting digital-based nursing care because they are confused and clumsy when operating the system. This is also caused by several factors, including age that is no longer young, because of a lack of knowledge about technology or technology failure, because it is new. This is the first time using digital-based nursing care. It would be better if digital skills literacy training among hospital employees, especially nurses, needs to be further improved by attending or holding webinars related to documenting digital nursing care.